Technology for preparation of thermal elements of SbBiTe alloys for thermoelectric coolers - Meglei, Dragoş (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)

(untitled)
An improved technology for treatment of thermal elements of SbBiTe alloys is given. Optimal technological regimes for their cutting, mechanical and chemical polishing are found. The electric spark method of cutting, double-sided mechanical polishing without preliminary grinding are found to improve the surface state, to increase output of valid thermal elements and to save material. Optimal conditions for chemical plating of nickel on butt-ends of thermal elements are found.